PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATA PELAJARAN TEKNIK DASAR OTOMOTIF DI SMK PIRI SLEMAN - Eko Arif Romdoni; Dianna Ratnawati (JURNAL VOKASI DEWANTARA (JVD), 2020)
ABSTRACT The purpose of the study (1) Increase activity class X student of SMK PIRI TKR Sleman on the subjects ofBasic Technique Automobile using NHT type cooperative model. (2) Improving the results of class X student of SMKPIRI TKR Sleman on the subjects of Basic Technique Automobile using NHT type cooperative model.This type of research used in this research is a class act. The subjects were students of class X SMK PIRITKR in Sleman by the number of 25 students.The data collection technique using observation and tests.Mechanicalanalysis using quantitative descriptive data analysis covering, Analysis of learning activities and analysis of studentlearning outcomes. The implementation of cooperative learning model type Numbered Head Together (NHT) can increase theactivity and student learning outcomes. It is seen from: (1) increased student learning activity seen in cycleI by 40%,the second cycle of 68%, and the third cycle of 80.80%; and (2) Increased student learning outcomes seen in thefirst cycle by 30% of students that reached KKM with an average grade of 54.25. In the second cycle by 55% ofstudents that reached KKM with an average grade of 72.50 While the learning outcomes of students in the thirdcycle was 85% of students that reached KKM with an average grade of 84.75.. Keywords: methods, activities, results.